Significance of Circulating Tumor Cells in Soft Tissue Sarcoma. (18th June 2015) - Nicolazzo, Chiara; Gradilone, Angela
Abstract : Circulating tumor cells can be detected from the peripheral blood of cancer patients. Their prognostic value has been established in the last 10 years for metastatic colorectal, breast, and prostate cancer. On the contrary their presence in patients affected by sarcomas has been poorly investigated. The discovery of EpCAM mRNA expression in different sarcoma cell lines and in a small cohort of metastatic sarcoma patients supports further investigations on these rare tumors to deepen the importance of CTC isolation. Although it is not clear whether EpCAM expression might be originally present on tumor sarcoma cells or acquired during the mesenchymal-epithelial transition, the discovery of EpCAM on circulating sarcoma cells opens a new scenario in CTC detection in patients affected by a rare mesenchymal tumor.